Artificial Intelligence and the Sustainability Paradox in an Age of Isolationism - Alexandru BODISLAV, Dumitru; BRAN, Florina; Elena PETRESCU, Irina; Mihai MATEESCU, Vicențiu (European Journal of Sustainable Development, 2025)
The landscape of government and politics is being transformed by Artificial Intelligence (AI), which is affecting both globalization and isolationism. This paper investigates the paradoxical role of AI in promoting deeper interconnectivity while concurrently strengthening isolationist tendencies among states. On the one hand, AI-driven automation, data analytics, and predictive modelling allow governments to improve domestic security, economic self-sufficiency, and nationalist rhetoric, thereby reducing their dependence on international cooperation. By perpetuating echo chambers and shaping public opinion, AI-powered disinformation campaigns and algorithmic biases further entrench isolationist ideologies. On the other hand, AI also expedites global governance mechanisms, enables international surveillance, and optimizes cross-border economic dependencies, thereby challenging the sustainability of isolationist policies. This study investigates the dual impact of AI by means of case studies, policy analysis, and computational modelling, emphasizing that AI can serve as both an instrument for political insularity and an agent of unavoidable globalization. The results indicate that, although AI enables governments to implement isolationist strategies more effectively, it also generates vulnerabilities that render absolute isolationism unsustainable in the long term. The paper concludes with policy recommendations for balancing AI's influence to maintain political stability while preserving international cooperation. Keywords: artificial intelligence, political isolationism, governance, nationalism, globalization, policy